Web-Based Gamelan Marketing Information System with CRM Strategy and New Product Delivery via Email at Sido Dadi Gamelan Industry in Jatiteken Village - Putri Wibowo, Armeta Eka; Purwanto, Eko; Permatasari , Hanifah (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The gamelan industry in Indonesia, as a rich and historical cultural heritage, faces significant challenges in sales and marketing, particularly in terms of efficiency and market reach. This article focuses on the implementation of information technology through the development of a web-based marketing information system supported by a Customer Relationship Management (CRM) strategy in the Sido Dadi Gamelan industry, located in Jatiteken Village, Sukoharjo Regency. This system is designed to facilitate more efficient and effective online sales, with a new product notification feature via email that is expected to expand market reach and enhance customer interaction. Additionally, the system aims to improve customer satisfaction through better relationship management, ultimately contributing to increased company profitability. The implementation of this information technology not only addresses the challenges faced by the gamelan industry but is also expected to strengthen the industry’s position in the global market through a more modern and structured marketing strategy.